The cytochrome c gene proximal enhancer drives activity-dependent reporter gene expression in hippocampal neurons - Delgado, Jary Y.; Owens, Geoffrey (Frontiers in Molecular Neuroscience, 2012)
The proximal enhancer of the cytochrome c gene (Cycs) contains binding sites for both cAMP response element binding proteins (CREB) and Nuclear Respiratory Factor 1 (NRF1). To investigate how neuronal activity regulates this enhancer region, a lentivirus was constructed in which a short-lived green fluorescent protein (GFP) was placed under the transcriptional control of the Cycs proximal enhancer. Primary hippocampal neurons were infected, and the synaptic strengths of individual neurons were measured by whole cell patch clamping. On average the amplitude of miniature postsynaptic currents (mEPSCs) was higher in brighter GFP+ neurons, while mEPSC frequencies were not significantly different. Inhibiting neural activity by applying a GABAA receptor agonist increased GFP expression in most neurons, which persisted after homeostatic synaptic scaling as evidenced by a decrease in the amplitude and frequency of mEPSCs. Removing the CREB binding sites revealed that calcium influx through L-type channels and NMDA receptors, and ERK1/2 activation played a role in NRF1-mediated transcription. CREB and NRF1 therefore combine to regulate transcription of Cycs in response to changing neural activity.